The implementation of Islamic Heritage Distribution in Community of Setu Subdistrict, South Tangerang Region - Sodikin Sodikin (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2021)
Islamic inheritance law is a law governing the distribution of inheritance left by the testator to the heirs, knowing the parts received from the inheritance for each heir who is entitled to receive it. In practice, what has happened in Setu Subdistrict, South Tangerang District, has not yet fully understood the inheritance system of Islam. The division of inheritance applied is a combination of Islamic inheritance with the customary inheritance of the local community, so that it still does not meet the requirements or conditions as an Islamic inheritance based on Sharia. Keyword: Division of Inheritance, Testator, Heir, Inheritance AbstrakHukum kewarisan Islam merupakan hukum yang mengatur tentang pembagian harta warisan yang ditinggalkan pewaris kepada ahli waris, dengan mengetahui bagian-bagian yang diterima dari peninggalan untuk setiap ahli waris yang berhak menerimanya. Dalam prakteknya yang terjadi di Kecamatan Setu Kota Tangerang Selatan belum sepenuhnya memahami secara utuh tentang sistem kewarisan Islam, hal ini terlihat dalam kehidupan sehari-harinya. Pembagian warisan yang diterapkan merupakan perpaduan antara kewarisan Islam dengan kewarisan adat masyarakat setempat, sehingga masih belum memenuhi ketentuan atau syarat sebagai suatu kewarisan Islam yang berlandaskan Syariah.Kata kunci: Pembagian Warisan, Pewaris, Ahli Waris, Harta Warisan